2015
DOI: 10.1136/bjophthalmol-2015-306869
|View full text |Cite
|
Sign up to set email alerts
|

Platinum segments: a new platinum chain for adjustable upper eyelid loading

Abstract: REC reference: 13/SW/0146. IRAS project ID: 119022.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…However, our earlier studies7 8 have demonstrated a higher morbidity associated with GWs. Additionally, the benefit of postoperative adjustability of PCs19 offers convenience and cost-effectiveness. Hence, PCs in the form of platinum segments have now become widely available at our hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our earlier studies7 8 have demonstrated a higher morbidity associated with GWs. Additionally, the benefit of postoperative adjustability of PCs19 offers convenience and cost-effectiveness. Hence, PCs in the form of platinum segments have now become widely available at our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The chosen weight (GW or PC) is sutured at a high-tarsal location 7 8 10 16 21. The method of assembly of platinum segments to form a PC has previously been described 19. Before 2013, we used 6-0 vicryl (polyglactin 910) sutures to fixate the weight to the superior tarsus border.…”
Section: Methodsmentioning
confidence: 99%
“…Осложнения, связанные с установкой пальпебральных имплантатов, подробно описаны в литературе [20][21][22][23]. Частота повторных хирургических вмешательств, а также таких осложнений, как существенное проминирование, экструзия, дислокация, воспаление и аллергическая реакция, после постановки имплантата из золота значительно выше в сравнении с таковой при постановке платинового имплантата [24,25]. Платина получила широкое распространение в качестве материала для имплантатов в разных областях медицины (кохлеарные имплантаты, коронарные стенты, ортопедическая стоматология, наночастицы) благодаря своей инертности, устойчивости к коррозии, биосовместимости и электрической проводимости [26][27][28].…”
Section: Discussionunclassified
“…Five studies reported the improvement in visual acuity. Three studies from Berghaus et al, 7 Malhotra et al, 8 and Kartush et al¹³ showed the improvement in visual acuity after the placement of the platinum chain and gold weight implants was 40-95%. The best improvement was reported in a study performed by Kartush et al 13 that showed an improvement of 95% of the average of + 2.4 lines by the gold weight implant technique.…”
Section: Improvement In Visual Acuity For Lid Loading Techniquementioning
confidence: 99%